Development of layered Titanate nanomaterials for environmental applications - Tang, Yuxin. (2013)
Nanosized materials with exceptional properties have already led to breakthroughs in various fields of science and technology. This project aims to explore new routes to design functional titanate nanomaterials with tailored structure to achieve low cost and efficient titanate materials for environmental cleanup, particularly water treatment methods and applications. Since the properties and applications of the nanomaterials greatly depend on their size, composition, crystal structure, morphology, as well as the surface functionality, the synthesis of the titanate materials and their hybrids with controlled structure, size, shape, and composition is very important to their various promising applications.